由教師課程意識探討學校本位統整課程的實踐行動School-based Integrated Curriculum Practical Actions: Case of Teacher Curriculum Consciousness - 李克難Ka-Nan Lee (Higher Education Foundation, 2008)
本文以詮釋學方法論述，從人的「意識」、行動與行為的意向意義、課程實踐行動的自由選擇、決定與教師課程意識覺醒，分析探究一所中學學校本位人文統整課程的締造與實施，以及教師課程意識與校本課程實踐行動相互激發，並討論以行事權、省思與協作等策略，幫助教師課程意識開展，促使學校課程實踐紮根，進而形塑相互學習的學校新文化，提供學生更豐富的學習與經驗，以達成自我實現。 This paper investigates the mutual stimulation of the development and administering of school-based integrated humanities curriculum for secondary schools and the realization of school-based curriculum from the intent and meaning of human consciousness, actions and behaviors; the free choice and decision of curriculum practical actions; and the curriculum consciousness of teachers in a hermeneutic approach. This paper also discussed promoting teacher curriculum consciousness development, school curriculum practice realization, and the establishment of a new school culture for mutual learning to provide students with more comprehensive learning and experiences by agency, reflection and collaboration strategies in order to achieve self-actualization.